Pengaruh Pemberian Aromaterapi Pappermint Terhadap Intensitas Mual Muntah Pasien Kanker Payudara Yang Menjalani Kemoterapi : Studi Kasus - Purbaningtyas, Sinta Ayu; Purwanti, Okti Sri (Universitas Pahlawan Tuanku Tambusai, 2024)
Cancer mamae is a malignant tumor as a cause of mortality and morbidity for women in both developing and developing countries. Chemotherapy is one of the treatments for cancer mamae patients. Nausea and vomiting are symptoms that patients often complain about during and after undergoing chemotherapy. Peppermint aromatherapy is a nursing intervention that can reduce the intensity of nausea and vomiting in patients who are undergoing chemotherapy. The aim of this study was to find out the effect of peppermint aromatherapy on the intensity of nausea and vomiting for cancer mamae patients caused by chemotherapy. Method: by inhaling the aroma of peppermint essential oil on cancer mamae patients 12 hours before the end of the chemotherapy process. The research design used a case study with a nursing care approach experienced by one managed patient who was given peppermint aromatherapy in order to know the intensity level of nausea and vomiting before being given aromatherapy and after being given aromatherapy. Keywords: cancer mamae, chemotherapy, nausea vomiting, aromatheraphy pappermint